Epidemiology and Burden of Lumbar Backache: A Cross-Sectional Study of Peripheral Populations - Haider Ali, Waheed Alam, Shakir Mahmood, Shafaat Hussain, Sohail Ahmad, Muhammad Mushtaq, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim and objective: To assess the burden of lumbar backache in the periphery of district Lakki Marwat. Materials and method: The current descriptive cross-sectional was conducted from December 2019 to July 2020 after the approval ethical review board in the periphery of the district Headquarter hospital of Lakki Marwat. A total of 846 participants were selected through a systematic random sampling technique by using the Rao soft calculator. The age of the participants was 25-75 years including both males and females. Informed consent was taken from each participant and a questionnaire was filled from each individual. All the data were collected and analyzed by using the latest version of SPSS 24. Results: A total of 846 participants of selected for the study aged 25-75 years. 26.12 % of the participants were from 46-55 years of age, however, 20.80 % were from 36-45 years of age. 513 (60.63 %) of them were male and 333 (39.36 %) of them were female participants. 22.93 % of them were house workers, 14.89 % of them were office boys, 22.34 % were students, and 10.16 % of them were health care professionals. 56.50 % had lumbar backache and 41.13 % had not experienced it. Table 4 indicates the numeric pain rating scale in which 35.98 % had mild, 44.56 %had moderate pain in addition, and 19.45 % had severe lumbar backache. Conclusion: The current study concluded that the overall burden of lumbar backache was 56.50 % among the participants, therefore, proper awareness among the people of peripheries in the district Lakki Marwat for the prevention of LBA and management are needed to prevent their disabilities in their future lives and maintain healthy lifestyles. Keywords: Lumbar backache, Numeric pain rating scale, back pain.